Quality of Life and Village Development: A Case Study from Lower Saxony, Germany - Harteisen, Ulrich; Eigner-Thiel, Swantje (Raumforschung und Raumordnung | Spatial Research and Planning, 2017)
In the context of demographic change there is currently an intensive discussion about how the quality of life can be maintained in villages with a shrinking population. In this paper, a spatial perspective is linked to the psychological concept of quality of life. The results of the qualitative empirical study in which 43 villagers in four Lower Saxony villages were asked how they themselves assess their quality of life in the village and where they see a need for action, their own opportunities for creativity and need for support are juxtaposed with existing and new approaches to village development. The result clearly shows that the village inhabitants attach great importance to social contacts in the village and that these, on the one hand, contribute directly to their own satisfaction with life, and on the other, also importantly constitute a basis for jointly shaping community matters and establishing good quality of life in the village. Based on these results, the authors recommend integrating social questions of village development more emphatically into village renewal plans, as well as further developing new support services. Overall, the research results emphasize the importance of the village community as a stimulus in civil society that deserves more attention as an important endogenous potential within village development.
Keywords: Research into village life; Quality of life; Village development; Demographic change; Rural development